Marital Beslag Outside Divorce Lawsuit in the Maqashid Syari’ah Perspective - Mulia, Riza (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
The law of marriage seeks to protect joint property in the marriage bond with the hope that a quality family can be formed without any problems. Rules in law provide various reasons for formal legal guarantees for the protection of joint assets. This reason also does not escape the view of Islamic law through maqashid syar'iyah. This paper uses a normative approach. The focus of the problem in this paper is the objective of applying marital beslag outside of a divorce suit from the viewpoint of maqashid syar'iyah. The results showed that the provisions for marital beslag outside of a divorce suit were intended to maintain human needs from the financial aspect of the family that could sustain the family. In this context, protection of property helps maintain relationships between individuals (families) through the meaning contained in the text, where confiscation contains an element of family care which is also the goal of the maqasid.